Urban hen legislation: Exposing an unexpected public health problem. Issue 3 (November 2022) - Martin, Wanda; Wagner, Lindsey; Marshall, Kerry
Urban hen keeping is one means for local food production, allowing for control over the supply. Many Canadian cities allow urban hens, while others are opposed to this form of urban agriculture. The purpose of this research was to understand the controversy of urban hens to support communities facing challenging futures. We report on the qualitative portion of a stepwise mixed methods study of 15 urban residents. Data consisted of semi-structured interviews and thematic analysis derived from open coding and selective coding based on a system change conceptual framework. Three main discourse areas on the struggle with urban hen bylaws included education on urban agriculture, differing values and visions for city life, and tensions between individual rights and the collective good.